In the Era of the Leeds Protocol: A Systematic Review and A Meta-Analysis on the Effect of Resection Margins on Survival Among Pancreatic Ductal Adenocarcinoma Patients. (March 2020) - Kurlinkus, B.; Ahola, R.; Zwart, E.; Halimi, A.; Yilmaz, B. S.; Ceyhan, G. O.; Laukkarinen, J.
Background and Aims: A positive resection margin is considered to be a factor associated with poor prognosis after pancreatic ductal adenocarcinoma resection. However, analysis of the resection margin is dependent on the pathological slicing technique. The aim of this systematic review and meta-analysis was to study the impact of resection margin on the survival of pancreatic ductal adenocarcinoma patients whose specimens were analyzed using the axial slicing technique. Material and Methods: A systematic search in the PubMed, Cochrane, and Embase datasets covering the time period from November 2006 to January 2019 was performed. Only studies with axial slicing technique (Leeds Pathology Protocol or Royal College of Pathology Protocol) were included in the final database. Meta-analysis between the marginal distance and survival was performed with the Inverse Variance Method in RevMan. Results: The systematic search resulted in nine studies meeting the inclusion criteria. The median survival for a resection margin 0 mm ranged from 12.3 to 23.4 months, for resection margin <0.5 mm 16 months, for resection margin <1 mm ranged from 11 to 27.5 months, for resection margin <1.5 mm ranged from 16.9 to 21.2 months, and for resection margin >2 mm ranged from 53.9 to 63.1 months. Five studies were eligible for meta-analysis. The pooled multivariable hazard ratio favored resection margin ⩾1 mm (hazard ratio: 1.32 and 95% confidence interval: 1.03–1.68, p = 0.03). Conclusion: Resection margins ⩾1 mm seem to lead to better survival in pancreatic ductal adenocarcinoma patients than resection margin <1 mm. However, there is not enough data to evaluate the effect of oncologic therapy or to analyze the impact of other resection margin distances on survival.